The Influence of Work Life Balance, Happiness At Work and Work Overload on Turnover Intention at PT Multi Garmenjaya Yogyakarta - Cahyaningrum, Ririn; Santosa, Awan (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This research effort aims to examine the influence of Work Life Balance, Happiness At Work and Work Overload on Turnover Intention at PT Multi Garmenjaya Yogyakarta. This research sample includes 107 employees employed at PT Multi Garmenjaya Yogyakarta. The methodology used for data collection involves the utilization of a survey approach with the use of research tools such as questionnaires. Data analysis requires the application of multiple linear regression to ensure the influence of each independent variable on Turnover Intention. The findings of this research reveal that (1) Work Life Balance shows a negative and significant influence on Turnover Intention, indicating that increasing the balance between work responsibilities and staff's personal lives leads to a reduced tendency to leave the organization. (2) Happiness At Work also has a negative and substantial influence on Turnover Intention, indicating that individuals who experience satisfaction and satisfaction in their work environment tend to have lower resignation intentions. (3) Work Overload has a positive and significant effect on Turnover Intention, indicating that the increase in workload felt by employees corresponds to an increase in the tendency to leave the organization. These results underscore the importance for companies to foster a harmonious and enjoyable work atmosphere while effectively managing employee workload to reduce Turnover Intention. Implementation of policies and initiatives that promote Work Life Balance and increase workplace satisfaction can serve as a viable approach to personnel retention.